PEMBELAJARAN FISIKA BERBASIS ALQUR'AN DALAM MENGHADAPI KOMPETISI SAINS MADRASAH (KSM) DI MAN 2 PADANGSIDIMPUAN - Togu Khairani (Yayasan Baitul Hikmah al-Zain, 2025)
This research examines the implementation of Qur'an-based physics learning in preparation for the Madrasah Science Competition (KSM) at MAN 2 Padangsidimpuan, North Sumatra. The main problem faced is the lack of integration between scientific concepts and Islamic values, which can affect student motivation and understanding. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and document analysis. The results showed that the use of a Qur'an-based learning approach can increase students' interest and understanding of physics concepts, because students can see the connection between science and religious teachings. This approach also motivates students to study harder in order to prepare for KSM. In addition, teachers play an important role in linking subject matter with Qur'anic values so that students can understand physics concepts holistically. The conclusion of this study is that the integration of physics learning with Qur'anic values can improve student motivation and learning outcomes. This approach is effective in preparing students to compete in KSM in a relevant and meaningful way. Further implementation is expected to optimise students' potential in science and faith